Enabling Distributed Intelligence with Ferroelectric Multifunctionalities. Issue 1 (31st October 2021) - Yao, Kui; Chen, Shuting; Lai, Szu Cheng; Yousry, Yasmin Mohamed
Abstract: Distributed intelligence involving a large number of smart sensors and edge computing are highly demanded under the backdrop of increasing cyber‐physical interactive applications including internet of things. Here, the progresses on ferroelectric materials and their enabled devices promising energy autonomous sensors and smart systems are reviewed, starting with an analysis on the basic characteristics of ferroelectrics, including high dielectric permittivity, switchable spontaneous polarization, piezoelectric, pyroelectric, and bulk photovoltaic effects. As sensors, ferroelectrics can directly convert the stimuli to signals without requiring external power supply in principle. As energy transducers, ferroelectrics can harvest multiple forms of energy with high reliability and durability. As capacitors, ferroelectrics can directly store electrical charges with high power and ability of pulse‐mode signal generation. Nonvolatile memories derived from ferroelectrics are able to realize digital processors and systems with ultralow power consumption, sustainable operation with intermittent power supply, and neuromorphic computing. An emphasis is made on the utilization of the multiple extraordinary functionalities of ferroelectrics to enable material‐critical device innovations. The ferroelectric characteristics and synergistic functionality combinations are invaluable for realizing distributed sensors and smart systems with energy autonomy. Abstract : Ferroelectric materials possess extraordinary multiple signal or energy conversion and storage functions, including high dielectric permittivity, switchable spontaneous polarization, piezoelectric, pyroelectric, and bulk photovoltaic effects. The characteristics of ferroelectrics, and the synergized combinations of their multiple functionalities are invaluable for realizing distributed wireless sensors and smart systems with energy autonomy.